Analisis Faktor-Faktor yang Mempengaruhi Produksi Usahatani Bawang Merah di Kecamatan Tawangmangu - Vita Intari Afrianika; Sri Marwanti; Isti Khomah (Universitas Muhammadiyah Malang, 2020)
The purpose of this research was to find out production factors affecting on the shallots production in Tawangmangu Subdistrict. The basic method used in this research was inferensial statistic. The determination of the sample area was purposive and the determination of respondents was accidental sampling with 60 farmers as respondents. The technique of collecting data was done by observation, interview, and recording. The data analysis method used Cobb-Douglas regression analysis model. The coefficient of determination (Adj R2) in this research is 0,631, which mean that 63,1% of shallots production in Tawangmangu Subdistrict could be explained by all factors in this research and the rest was explained by other factors. F test result of variable land area, labor, number of seeds, manure, nitrogen fertilizer, phosphorus fertilizer, potassium fertilizer and pesticides simultaneously have an significant effect on the shallots production in Tawangmangu Subdistrict. t test result of land area, number of seeds and pesticides individually have a significant effect on production, while labor, manure, nitrogen fertilizer phosphorus fertilizer and potassium fertilizer individually have no significant effect on the shallots production in Tawangmangu Subdistrict. Land area variable is the most influences factor on the shallots production in Tawangmangu Subdistrict.